A biodegradable composite active film and its preparation method and application
By using a composite active film composed of modified hydroxyethyl cellulose, nanosilicon dioxide and plulandosaccharide in food packaging materials, the problems of existing plastic packaging materials pollution to the environment and food shelf life are solved, and biodegradation, antioxidant and antibacterial effects are achieved.
Patent Information
- Application Number
- CN202211441374.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-17
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2042-11-17
AI Technical Summary
Existing food packaging materials are mainly non-degradable plastics, which lead to environmental pollution, and it is difficult to effectively control moisture loss and chemical reactions, affecting food quality and safety.
A biodegradable composite active film consisting of modified hydroxyethyl cellulose, nanosilica and plulandosaccharides, and a film with antioxidant, antibacterial and good mechanical properties is formed by the use of silane coupling agents and crosslinking agents.
It achieves a low water vapor permeability coefficient, good antioxidant and antibacterial activity, can biodegradation, avoid environmental pollution, and extend the shelf life of food.
Smart Images

Figure CN116217987B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of food packaging materials, and in particular to a biodegradable composite active film and a preparation method and application thereof. Background Art
[0002] Packaging can effectively extend the preservation and shelf life of fruits, vegetables and processed foods. The progress of industrialization has led to a sharp increase in the use of plastics for food packaging. Plastics are very convenient as packaging materials due to their low price, high mechanical strength, easy molding, good heat sealing and light weight, but the large-scale use of plastic packaging materials may have an adverse impact on the environment. Therefore, it is crucial to seek degradable plastic wrap. The main function of plastic wrap is to control water loss and reduce the rate of adverse chemical reactions to improve the quality and safety of various processed foods and fresh foods. The addition of various food additives, such as antimicrobial agents and antioxidants, to the film matrix further expands their application. The use of natural degradable biopolymers to replace non-degradable chemical materials has become a research hotspot in the field of food packaging. Summary of the invention
[0003] The technical problem to be solved by the present invention is to provide a biodegradable composite active membrane, which has a low water vapor permeability coefficient, good antioxidant and antibacterial activity, is biodegradable, can avoid environmental pollution and achieve a good preservation effect.
[0004] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0005] The first aspect of the present invention provides a method for preparing a biodegradable composite active film, comprising the following steps:
[0006] S1. Mixing and stirring a silane coupling agent and a hydroxyethyl cellulose solution to obtain an amino-hydroxyethyl cellulose solution; then, activating the carboxyl group in the modifier, adding the activated modifier to the amino-hydroxyethyl cellulose solution, heating and stirring until the reaction is complete; after centrifugation, washing, and freeze-drying, powdered modified hydroxyethyl cellulose is obtained; wherein the modifier is cinnamic acid, hydroxycinnamic acid, and its derivatives;
[0007] S2. The modified hydroxyethyl cellulose is prepared into a solution, tetraethyl orthosilicate is added dropwise, and stirred to form a gel;
[0008] S3. The gel is cast into a film, washed with water, and vacuum dried to obtain a modified hydroxyethyl cellulose / SiO2 film;
[0009] S4. Prepare a film-forming liquid with Prussian polysaccharide and glycerol, and perform ultrasonic degassing; immerse the modified hydroxyethyl cellulose / SiO2 membrane in the film-forming liquid, and add a cross-linking agent for cross-linking; and dry after the reaction to obtain the biodegradable composite active membrane.
[0010] Hydroxyethyl cellulose (HEC) is a cellulose derivative with good water solubility and film-forming properties. Its molecules contain a large number of hydroxyl groups, making it easy to be chemically modified. Cinnamic acid, also known as cinnamic acid, can be extracted from various plants such as benzoin, has good antibacterial and antioxidant effects, and is gradually being developed and utilized in many fields. In the present invention, cinnamic acid is used to modify hydroxyethyl cellulose, which can retain the original film-forming properties of hydroxyethyl cellulose while giving it good antibacterial and antioxidant properties.
[0011] Nano silicon dioxide has a large specific surface area, light weight, high temperature resistance and stable chemical properties. It has the characteristic of small particle size of nano materials, can penetrate into polymer compounds, cross-link with polymer materials to form a spatial network structure, and then improve the overall performance of the material. However, since the particle size of nano silicon dioxide is very small and the surface energy is high, it is easy to agglomerate when directly added to the film-forming liquid. Even if it is treated by means such as ultrasound, it is difficult to make it dispersed evenly in the film, which will affect the mechanical properties of the film. In the present invention, by the hydrolysis of tetraethyl orthosilicate, nano-scale silicon dioxide of uniform size can be formed in situ in the gel, and the nano silicon dioxide is very evenly distributed in the gel, which greatly improves the mechanical properties of the composite film.
[0012] Pullulan (PUL) is a linear polymer composed of maltotriose units interconnected by α-(1,6) glycosidic bonds. It has good barrier properties, antibacterial properties, antioxidant capacity, etc., and is an excellent film-forming material. In the present invention, pullulan is used to form a film on the surface of a modified hydroxyethyl cellulose / SiO2 film, and a cross-linking agent is used to cross-link it, which not only improves the mechanical properties of the composite film, but also significantly increases its tensile strength and elongation at break, and the water vapor permeability of the composite film is greatly reduced, while the antibacterial and antioxidant properties are also improved.
[0013] Further, in step S1, the preparation method of the amino-hydroxyethyl cellulose solution is: ultrasonically dispersing hydroxyethyl cellulose in a mixed solvent of ethanol and water, adding a silane coupling agent, and continuously stirring to obtain the amino-hydroxyethyl cellulose solution; wherein the ratio of the hydroxyethyl cellulose, the mixed solvent and the silane coupling agent is (5-10): (50-80): (1.5-3) g: mL: mL; the power of the ultrasonic dispersion is 300-600 W, and the ultrasonic time is 15-30 min. The silane coupling agent is a silane coupling agent with an amino group, such as 3-aminopropyltriethoxysilane (KH550).
[0014] In the present invention, the siloxane end groups in the silane coupling agent are hydrolyzed to generate silanol groups, which can bond with the hydroxyl functional groups on the surface of hydroxyethyl cellulose, thereby introducing amino functional groups on the surface of hydroxyethyl cellulose to facilitate the subsequent grafting of modifiers such as cinnamic acid.
[0015] Furthermore, in step S1, the activation treatment is: dissolving the modifier in an organic solvent, adding EDC and NHS as activators, and stirring to activate the carboxyl group in the modifier; wherein the ratio of the modifier, the organic solvent, EDC and NHS is (0.5-1.2): (50-75): (2-4.5): (1-2.5) g:mL:mL:mL.
[0016] Furthermore, in step S1, the mass ratio of hydroxyethyl cellulose to modifier is 5-10:0.5-1.2.
[0017] Furthermore, in step S1, freeze drying is performed in a vacuum freeze dryer with a vacuum degree of 0.01-0.02 MPa and a drying temperature of -50-60°C.
[0018] Furthermore, in step S2, the method for forming a gel is: ultrasonically dispersing modified hydroxyethyl cellulose in a mixed solvent of ethanol and water, adding tetraethyl orthosilicate dropwise thereto, stirring while adding dropwise, until a gel is formed; wherein the ratio of modified hydroxyethyl cellulose, mixed solvent, and tetraethyl orthosilicate is (3-6):(40-60):(0.5-2) g:mL:mL.
[0019] In the above-mentioned mixed solvent of ethanol and water, the volume ratio of ethanol to water is preferably 4:6 to 6:4, for example 4:6, 5:5, 6:4, etc.
[0020] Further, in step S3, the vacuum degree of vacuum drying is 0.01-0.02MPa, the drying temperature is 60-80°C, and the drying time is 8-12h;
[0021] Furthermore, in step S3, the in-situ generated SiO2 is spherical with a diameter of 50-100 nm, and the loading amount on the modified hydroxyethyl cellulose is preferably 5-11 wt%, for example, 5 wt%, 6 wt%, 7 wt%, 8 wt%, 9 wt%, 10 wt%, or 11 wt%.
[0022] Furthermore, in step S4, the preparation method of the film-forming liquid is: dissolving pullulan in water, adding glycerol, and stirring to form a pullulan film-forming liquid; wherein the ratio of pullulan, water and glycerol is (1.5-3): (20-45): (0.3-0.6) g:mL:g; the stirring is preferably magnetic stirring, the stirring speed is preferably 450-750r / min, and the stirring time is preferably 3-8h.
[0023] Further, in step S4, the cross-linking agent includes but is not limited to at least one of glutaraldehyde, glyoxal, epichlorohydrin, and sodium tripolyphosphate. The added amount of the cross-linking agent is preferably 5wt% to 10wt% of the pullulan, for example, 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, or 10wt%.
[0024] Furthermore, in step S4, the power of ultrasonic degassing is preferably 120-250 W, and the time is preferably 5-10 min; the drying temperature is preferably 45-80° C., and the drying time is preferably 16-18 h.
[0025] Furthermore, in step S4, the ratio of modified hydroxyethyl cellulose, tetraethyl orthosilicate, pullulan, and glycerol is 3-6:0.5-2:1.5-3:0.3-0.6 g:mL:g:g.
[0026] The second aspect of the present invention provides a biodegradable composite active film prepared by the above method.
[0027] The third aspect of the present invention provides the use of the above-mentioned biodegradable composite active film as a fresh-keeping film.
[0028] Compared with the prior art, the present invention has the following beneficial effects:
[0029] 1. The modified hydroxyethyl cellulose prepared by the method of the present invention retains the advantages of hydroxyethyl cellulose itself and has antibacterial and antioxidant properties.
[0030] 2. The composite active membrane prepared by the method of the present invention directly generates silicon dioxide nanoparticles in the cellulose substrate and cross-links with pullulan. Compared with a single membrane, it has better mechanical properties and low water vapor permeability coefficient, and can achieve better antibacterial and antioxidant effects.
[0031] 3. During the production process of the present invention, the materials are environmentally friendly and non-toxic, and can be naturally degraded, which can alleviate the environmental pressure brought by petroleum-based plastic packaging materials, avoid pollution to the environment, and extend the shelf life of food. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 It is the DPPH radical scavenging rate of the membranes prepared in Examples 1-3 and Comparative Examples 1-3.
[0033] Figure 2 The inhibition zones of the films prepared in Examples 1-3 and Comparative Examples 1-3 are: a. Example 1; b. Example 2; c. Example 3; d. Comparative Example 1; e. Comparative Example 2; f. Comparative Example 3.
[0034] Figure 3 is the diameter of the inhibition zone of the films prepared in Examples 1-3 and Comparative Examples 1-3;
[0035] Figure 4 The degradability of the films prepared in Examples 1-3 and Comparative Examples 1-3. DETAILED DESCRIPTION
[0036] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.
[0037] The present invention is further described below in conjunction with specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.
[0038] Unless otherwise specified, the experimental methods used in the following examples are conventional methods.
[0039] Example 1
[0040] A method for preparing a biodegradable antibacterial and antioxidant composite active film comprises the following steps:
[0041] 5g of hydroxyethyl cellulose was ultrasonically dispersed in a mixed solvent of 50mL of ethanol and water (volume ratio 4:6) at a power of 400W, and then 1.5mL of 3-aminopropyltriethoxysilane was added to the mixed solvent, and the mixture was stirred at a temperature of 60°C and a stirring speed of 750r / min for 8h to obtain an amino-hydroxyethyl cellulose solution. 500mg of cinnamic acid was dissolved in 75mL of DMF, and 2mL of EDC and 1mL of NHS were added as activators to activate the carboxyl group at 4°C for 40min. The activated silicic acid was added to the amino-hydroxyethyl cellulose solution, stirred at 450r / min for 6h, and then centrifuged and washed to obtain modified hydroxyethyl cellulose.
[0042] 3g of modified hydroxyethyl cellulose was ultrasonically dispersed in 40mL of a mixed solvent of ethanol and water (volume ratio 4:6) at a power of 400W, and 0.5mL of tetraethyl orthosilicate was added thereto. The mixture was stirred at a temperature of 45°C and a stirring speed of 600r / min for 6 hours until a gel was formed. The gel was cast onto a glass plate with a thickness of 0.5mm, washed with deionized water, and dried in a vacuum oven at 60°C for 12 hours to obtain a modified hydroxyethyl cellulose / SiO2 film.
[0043] 1.5g of pullulan was dissolved in 20mL of deionized water, and 0.3g of glycerol was added thereto. The stirring speed was 450r / min, and the stirring was continued for 3h to obtain a pullulan film-forming liquid. The film was ultrasonically degassed for 10min at a power of 120W, and the degassed film-forming liquid was poured onto a polypropylene plate. The modified hydroxyethyl cellulose / SiO2 membrane prepared above was then immersed in the pullulan film-forming liquid, and 1% glutaraldehyde (the added amount was 5wt% of the pullulan content) was added thereto for cross-linking. After the reaction was completed, it was dried at high temperature for 16h to obtain a composite membrane.
[0044] Example 2
[0045] A method for preparing a biodegradable antibacterial and antioxidant composite active film comprises the following steps:
[0046] 7g of hydroxyethyl cellulose was ultrasonically dispersed in a 60mL mixed solvent solution of ethanol and water (volume ratio 4:6) at a power of 400W, and then 2mL of 3-aminopropyltriethoxysilane was added to the mixed solvent, and the temperature was 60°C, the stirring speed was 750r / min, and the stirring was continued for 8h to obtain an amino-hydroxyethyl cellulose solution. 800mg of cinnamic acid was dissolved in 75mL of DMF, and 2mL of EDC and 1mL of NHS were added as activators to activate the carboxyl group at 4°C for 40min. The activated silicic acid was added to the above amino-hydroxyethyl cellulose solution, and the solution was stirred at 450r / min for 6h and then centrifuged and washed to obtain modified hydroxyethyl cellulose.
[0047] 4g of modified hydroxyethyl cellulose was ultrasonically dispersed in 50mL of a mixed solvent of ethanol and water (volume ratio 4:6) at a power of 400W, and 1mL of tetraethyl orthosilicate was added thereto. The mixture was stirred at a temperature of 45°C and a stirring speed of 600r / min for 6 hours until a gel was formed. The gel was cast onto a glass plate with a thickness of 0.5mm, washed with deionized water, and dried in a vacuum oven at 60°C for 12 hours to obtain a modified hydroxyethyl cellulose / SiO2 film.
[0048] 2g of pullulan was dissolved in 25mL of deionized water, and 0.4g of glycerol was added thereto. The stirring speed was 450r / min, and the stirring was continued for 3h to obtain a pullulan film-forming liquid. The film was ultrasonically degassed for 10min at a power of 120W, and the degassed film-forming liquid was poured onto a polypropylene plate. The modified hydroxyethyl cellulose / SiO2 membrane prepared above was then immersed in the pullulan film-forming liquid, and 1% glutaraldehyde (the added amount was 5wt% of the pullulan content) was added thereto for cross-linking. After the reaction was completed, it was dried at high temperature for 16h to obtain a composite membrane.
[0049] Example 3
[0050] A method for preparing a biodegradable antibacterial and antioxidant composite active film comprises the following steps:
[0051] 10g of hydroxyethyl cellulose was ultrasonically dispersed in a mixed solvent of 75mL of ethanol and water (volume ratio 4:6) at a power of 400W, and then 3mL of 3-aminopropyltriethoxysilane was added to the mixed solvent, and the mixture was stirred at a temperature of 60°C and a stirring speed of 750r / min for 8h to obtain an amino-hydroxyethyl cellulose solution. 1.2g of cinnamic acid was dissolved in 75mL of DMF, and 2mL of EDC and 1mL of NHS were added as activators to activate the carboxyl group at 4°C for 40min. The activated silicic acid was added to the amino-hydroxyethyl cellulose solution, stirred at 450r / min for 6h, and then centrifuged and washed to obtain modified hydroxyethyl cellulose.
[0052] 6g of modified hydroxyethyl cellulose was ultrasonically dispersed in 60mL of a mixed solvent of ethanol and water (volume ratio 4:6) at a power of 400W, and 2mL of tetraethyl orthosilicate was added thereto. The mixture was stirred at a temperature of 45°C and a stirring speed of 600r / min for 6 hours until a gel was formed. The gel was cast onto a glass plate with a thickness of 0.5mm, washed with deionized water, and dried in a vacuum oven at 60°C for 12 hours to obtain a modified hydroxyethyl cellulose / SiO2 film.
[0053] 3g of pullulan was dissolved in 30mL of deionized water, and 0.6g of glycerol was added thereto. The stirring speed was 450r / min and the stirring was continued for 3h to obtain a pullulan film-forming liquid. The film was ultrasonically degassed for 10min at a power of 120W, and the degassed film-forming liquid was poured onto a polypropylene plate. The modified hydroxyethyl cellulose / SiO2 membrane prepared above was then immersed in the pullulan film-forming liquid, and 1% glutaraldehyde (the added amount was 5wt% of the pullulan content) was added thereto for cross-linking. After the reaction was completed, the film was dried at high temperature for 16h to obtain a composite membrane.
[0054] Comparative Example 1
[0055] A method for preparing a hydroxyethyl cellulose / SiO2 film comprises the following steps:
[0056] 6g of hydroxyethyl cellulose was ultrasonically dispersed in 40mL of a mixed solvent of ethanol and water (volume ratio 4:6) at a power of 400W, and 1.5mL of tetraethyl orthosilicate was added. The mixture was stirred at a temperature of 45°C and a speed of 600r / min for 6 hours until a gel was formed. The gel was cast onto a glass plate with a thickness of 0.5mm, washed with deionized water, and dried in a vacuum oven at 60°C for 12 hours to obtain a hydroxyethyl cellulose / SiO2 film.
[0057] Comparative Example 2
[0058] A method for preparing a modified hydroxyethyl cellulose / SiO2 film comprises the following steps:
[0059] 5g of hydroxyethyl cellulose was ultrasonically dispersed in a mixed solvent of 50mL of ethanol and water (volume ratio 4:6) at a power of 400W, and then 1.5mL of 3-aminopropyltriethoxysilane was added to the mixed solvent, and the mixture was stirred at a temperature of 60°C and a stirring speed of 750r / min for 8h to obtain an amino-hydroxyethyl cellulose solution. 500mg of cinnamic acid was dissolved in 75mL of DMF, and 2mL of EDC and 1mL of NHS were added as activators to activate the carboxyl group at 4°C for 40min. The activated silicic acid was added to the amino-hydroxyethyl cellulose solution, stirred at 450r / min for 6h, and then centrifuged and washed to obtain modified hydroxyethyl cellulose.
[0060] 3g of modified hydroxyethyl cellulose was ultrasonically dispersed in 40mL of a mixed solvent of ethanol and water (volume ratio 4:6) at a power of 400W, and 0.5mL of tetraethyl orthosilicate was added thereto. The mixture was stirred at a temperature of 45°C and a stirring speed of 600r / min for 6 hours until a gel was formed. The gel was cast onto a glass plate with a thickness of 0.5mm, washed with deionized water, and dried in a vacuum oven at 60°C for 12 hours to obtain a modified hydroxyethyl cellulose / SiO2 film.
[0061] Comparative Example 3
[0062] A method for preparing a pullulan film comprises the following steps:
[0063] 2 g of pullulan was dissolved in 25 mL of deionized water, to which 0.4 g of glycerol was added, and stirring was continued for 3 h at a stirring speed of 450 r / min to obtain a pullulan film-forming solution. The solution was ultrasonically degassed at a power of 120 W for 10 min, and the degassed film-forming solution was poured onto a polypropylene plate and dried at high temperature for 16 h to obtain a pullulan film.
[0064] Composite membrane performance test and effect verification
[0065] 1. According to GB13022-91 "Test method for tensile properties of plastic films", the tensile strength and elongation at break of the film were measured using a universal testing machine.
[0066] (1) The tensile strength (TS) is calculated as shown in Formula 1:
[0067] TS=F MAX / (L×W) (Formula 1)
[0068] TS represents the tensile strength (Mpa), Fmax is the maximum tensile force that the membrane withstands when it breaks, L represents the width of the membrane, and W represents the thickness of the membrane.
[0069] (2) Elongation at break (EB%) is calculated as shown in Formula 2:
[0070] EB%=(L-L0) / L0 (Formula 2)
[0071] L represents the initial length of the film (mm), and L0 represents the length of the film after stretching (mm).
[0072] 2. Test the water vapor permeability of the film according to GB1307-88 "Test Method for Water Vapor Permeability of Plastic Film and Sheet - Cup Method". The specific operation is to add dried anhydrous calcium chloride into the moisture permeability cup, 5mm away from the bottle mouth, tie the bottle mouth with the prepared plastic wrap and seal it with paraffin, place it in a dryer with saturated sodium chloride solution at the bottom, take out the weighing bottle and weigh it at regular intervals until the difference between the mass increase before and after is less than 5%, weigh it three times, and calculate the average value, as shown in Formula 3:
[0073] WVP=Δm×d / (A×Δt×Δp) (Formula 3)
[0074] Where WVP is the water vapor transmission coefficient [g·mm / (m 2·h·kPa)]; d is the thickness of the composite film (mm); Δm is the mass increase after stabilization (g); A is the area of the cut film (m 2 ), Δt represents the time interval between each measurement (h), Δp represents the fixed water vapor pressure difference on both sides of the composite membrane (kPa), the experimental temperature is 25°C, and the relative humidity is maintained at 75%.
[0075] Table 1 Mechanical properties and water vapor permeability coefficients of the composite films prepared in Examples 1-3 and Comparative Examples 1-3
[0076]
[0077] Table 1 shows the mechanical properties and water vapor permeability coefficient of the composite cling film prepared by Comparative Examples 1-3 and Examples 1-3. As can be seen from Table 1, compared with the single film and composite film in Comparative Examples 1-3, in Examples 1-3, as the content of modified hydroxyethyl cellulose, tetraethyl orthosilicate, and pullulan increases, the tensile strength and elongation at break of the composite film gradually increase, while the water permeability coefficient gradually decreases. This is because the formation of SiO2 in the film substrate and the cross-linking of the composite film and pullulan make the film structure more compact.
[0078] 3. Use DPPH free radical scavenging experiment to determine the antioxidant property of the film. The specific operation is: cut the film into 3cm×3cm square pieces and put them into 50mL 50% ethanol solution, centrifuge for 30 minutes, take 3mL of extract and 1mL DPPH ethanol solution (0.1mM) respectively, mix them, and react for 30 minutes in the dark. Then use ultraviolet spectrophotometer to measure the absorbance at 517nm, and do three parallels for each sample. The results are as follows: Figure 1 The calculation formula of free radical scavenging rate (%) is as follows:
[0079]
[0080] In the formula:
[0081] A0: absorbance value of DPPH working solution;
[0082] A s : Absorbance value after adding sample solution.
[0083] Figure 1 is the DPPH free radical scavenging rate of the composite membranes prepared in Examples 1-3 and Comparative Examples 1-3. Figure 1It can be seen that the DPPH radical scavenging rate of the single film in Comparative Example 1 is basically the same, which indicates that hydroxyethyl cellulose itself has no obvious antioxidant activity, and the formation of silicon dioxide has basically no significant effect on the antioxidant property of the film. In contrast, the DPPH radical scavenging rate of the composite film in Examples 1-3 increases with the increase of the content of cinnamic acid and modified hydroxyethyl cellulose, which indicates that the modification of hydroxyethyl cellulose by cinnamic acid improves the antioxidant property of the composite film, and cinnamic acid and pullulan can play a synergistic antioxidant role.
[0084] 4. Use the inhibition zone experiment to determine the antibacterial properties of the prepared film. The specific operation is: Escherichia coli frozen at -80℃ is activated on a solid LB plate by streaking, a single colony is picked and inoculated into 10mL liquid LB, and it is placed in a 37℃ shaker for 12 hours to make the bacteria in the late logarithmic growth stage. The bacterial solution is diluted (about 10 -3 CFU / mL) and then evenly spread it on a solid LB plate. Place a 6mm diameter membrane on the plate and place the plate in a 37℃ constant temperature incubator for 14 to 16 hours. Measure the diameter of the inhibition zone. The results are as follows Figure 2-3 shown.
[0085] Figure 2-3 are the inhibition zones and their diameters of the films prepared in Examples 1-3 and Comparative Examples 1-3. Figure 2 It can be seen that the single film of comparative example 1 has almost no inhibitory effect on Escherichia coli. However, Examples 1-3 have a significant inhibitory effect on Escherichia coli, which shows that the modification of hydroxyethyl cellulose by cinnamic acid significantly improves its antibacterial ability, and through cross-linking with pullulan, a synergistic effect further improves the antibacterial activity. In addition, the inhibition zone of the composite membranes in Examples 1-3 gradually expands with the increase of the content of modified hydroxyethyl cellulose, which shows that modified hydroxyethyl cellulose can improve the antibacterial performance of the composite membranes.
[0086] 5. The prepared films were subjected to degradation experiments and qualitatively evaluated at 25°C to assess their biodegradability. The films (25 mm × 25 mm) were buried in a rectangular plastic pot filled with vegetable compost to a depth of 10 mm and sprayed with water every day to maintain humidity. The surrounding environment was strictly controlled throughout the test. After one month, film samples were extracted from the soil and photographed to determine their biodegradability. The integrity of the prepared films was observed by visual methods, and the results were as follows: Figure 4 shown.
[0087] Figure 3The macroscopic appearance changes of the films prepared by Examples 1-3 and Comparative Examples 1-3 in vegetable compost over time are shown. As can be seen from the above figure, the films of Comparative Examples 1-3 and Examples 1-3 all degraded after one month. In contrast, the polyethylene film maintained its original structure throughout the experiment without any obvious damage. This shows that both pullulan and hydroxyethyl cellulose can be naturally degraded, and the composite film prepared therefrom can also be degraded in the natural environment. This composite film with high biodegradability can be an excellent substitute for polyethylene film.
[0088] The above-described embodiments are only preferred embodiments for fully illustrating the present invention, and the protection scope of the present invention is not limited thereto. Equivalent substitutions or changes made by those skilled in the art based on the present invention are within the protection scope of the present invention. The protection scope of the present invention shall be subject to the claims.
Claims
1. A method for preparing a biodegradable composite active film, characterized in that: The following steps are involved: S1. Mixing and stirring a silane coupling agent and a hydroxyethyl cellulose solution to obtain an amino-hydroxyethyl cellulose solution; then, activating the carboxyl group in the modifier, and adding the activated modifier to the amino-hydroxyethyl cellulose solution, heating and stirring until the reaction is complete; after centrifugation, washing, and freeze-drying, powdered modified hydroxyethyl cellulose is obtained; wherein the modifier is cinnamic acid and / or hydroxycinnamic acid; the preparation method of the amino-hydroxyethyl cellulose solution is: ultrasonically dispersing hydroxyethyl cellulose in a mixed solvent of ethanol and water, adding a silane coupling agent, and continuously stirring to obtain the amino-hydroxyethyl cellulose solution; wherein the ratio of the hydroxyethyl cellulose, the mixed solvent, and the silane coupling agent is (5-10): (50-80): (1.5-3) g : mL : mL; S2. The modified hydroxyethyl cellulose is prepared into a solution, tetraethyl orthosilicate is added dropwise, and the solution is stirred to form a gel; the method for forming the gel is: the modified hydroxyethyl cellulose is ultrasonically dispersed in a mixed solvent of anhydrous ethanol and water, tetraethyl orthosilicate is added dropwise thereto, and the solution is stirred while being added dropwise until a gel is formed; wherein the ratio of the modified hydroxyethyl cellulose, the mixed solvent, and tetraethyl orthosilicate is (3-6): (40-60): (0.5-2) g : mL : mL; S3. The gel was cast into a film, washed with water, and vacuum dried to obtain a modified hydroxyethyl cellulose / SiO2 film; S4. Prepare pullulan and glycerol into a film-forming liquid, and degas by ultrasonic treatment; immerse the modified hydroxyethyl cellulose / SiO2 membrane in the film-forming liquid, and add a cross-linking agent for cross-linking; after the cross-linking reaction is completed, take out the membrane material, and dry it to obtain the biodegradable composite active membrane; the preparation method of the film-forming liquid is: dissolve pullulan in water, add glycerol, and stir to form a pullulan film-forming liquid; wherein the ratio of pullulan, water and glycerol is (1.5-3): (20-45): (0.3-0.6) g: mL: g.
2. The method for preparing a biodegradable composite active film according to claim 1, characterized in that: In step S1, the power of the ultrasonic dispersion is 300-600W, and the ultrasonic time is 15-30min; the silane coupling agent is a silane coupling agent with amino groups.
3. The method for preparing a biodegradable composite active film according to claim 1, characterized in that: In step S1, the activation treatment is as follows: dissolving the modifier in an organic solvent, adding EDC and NHS as activators, and stirring to activate the carboxyl group; Among them, the ratio of modifier, organic solvent, EDC and NHS is (0.5-1.2):(50-75):(2-4.5):(1-2.5) g:mL:mL:mL.
4. The method for preparing a biodegradable composite active film according to claim 1, characterized in that: In step S1, the freeze drying is carried out in a vacuum freeze dryer with a vacuum degree of 0.01-0.02 MPa and a drying temperature of -50-60°C.
5. The method for preparing a biodegradable composite active film according to claim 1, characterized in that: In step S3, the vacuum degree of the vacuum drying is 0.01-0.02MPa, the drying temperature is 60-80°C, and the drying time is 8-12h; The SiO2 is spherical, with a diameter of 50-100 nm, and a loading amount on the modified hydroxyethyl cellulose of 5-11 wt %.
6. The method for preparing a biodegradable composite active film according to claim 1, characterized in that: In step S4, the stirring is magnetic stirring, the stirring speed is 450-750 r / min, and the stirring time is 3-8 h.
7. The method for preparing a biodegradable composite active film according to claim 1, characterized in that: In step S4, the cross-linking agent is at least one of glutaraldehyde, glyoxal, epichlorohydrin, and sodium tripolyphosphate, and the added amount of the cross-linking agent is 5wt% to 10wt% of the pullulan; The power of the ultrasonic degassing is 120-250W, and the time is 5-10min; the drying temperature is 45-80°C, and the drying time is 16-18h.
8. The biodegradable composite active film prepared by the method according to any one of claims 1 to 7.
9. Use of the biodegradable composite active film according to claim 8 as a fresh-keeping film.
Citation Information
Patent Citations
Polysaccharide-base gel composite film, and preparation method and application thereof
CN105733031A
Carboxymethyl chitosan / bacterial cellulose / nano silicon dioxide active packaging film and preparation method thereof
CN114369292A